ETNOSAINS PERKEBUNAN SINGKONG: STUDI LITERATUR INTEGRASI BUDAYA LOKAL DALAM PEMBELAJARAN IPAS SEKOLAH DASAR DI TULANG BAWANG LAMPUNG - Luthfiana Luthfiana; Eko Handoyo; Hanafi Hussin (ELEMENTARY: Jurnal Inovasi Pendidikan Dasar, 2026)
The limited integration of local cassava-based ethnoscience in elementary IPAS learning has caused science and social studies materials to be less connected to students’ cultural experiences, agrarian environment, and daily lives, particularly in Tulang Bawang, Lampung. This study aims to analyze the forms of integration of cassava plantation ethnoscience into elementary IPAS learning through a literature review. The literature search was conducted through Google Scholar, SINTA, Scopus, and Garuda, as well as supporting academic sources, including books, journal articles, proceedings, and research reports. The literature was selected based on the criteria of publications from 2014 to 2025, relevance to ethnoscience, elementary IPAS/science learning, local culture, local wisdom, contextual learning, cassava cultivation or processing practices, and availability in full text. The data were analyzed using descriptive-thematic analysis through the identification, classification, mapping, and interpretation of key themes related to local community practices and IPAS concepts. The findings show that cassava plantation ethnoscience can be integrated into IPAS learning through three main forms: conceptual integration, contextual integration, and cultural value integration. Conceptual integration is reflected in the mapping of local practices, such as seed selection, stem cutting, soil preparation, plant maintenance, cassava tape fermentation, gaplek drying, and tapioca flour production, with the concepts of plant growth, ecosystems, changes in matter, and production processes. Contextual integration is carried out by utilizing cassava plantations, agricultural environments, and home industries as learning resources. Cultural value integration includes the internalization of hard work, mutual cooperation, economic independence, and environmental care. The implication of this study highlights the need to develop systematic, contextual, and student-appropriate cassava ethnoscience-based IPAS learning materials that suit the characteristics of elementary school students in Tulang Bawang. ABSTRAK Minimnya integrasi etnosains lokal singkong dalam pembelajaran IPAS sekolah dasar menyebabkan materi sains dan sosial kurang terhubung dengan pengalaman budaya, lingkungan agraris, dan kehidupan sehari-hari siswa, khususnya di Tulang Bawang, Lampung. Penelitian ini bertujuan menganalisis bentuk integrasi etnosains perkebunan singkong dalam pembelajaran IPAS sekolah dasar melalui studi literatur. Penelusuran literatur dilakukan melalui Google Scholar, SINTA, Scopus, dan Garuda, serta sumber akademik pendukung berupa buku, artikel jurnal, prosiding, dan laporan penelitian. Literatur dipilih berdasarkan kriteria publikasi tahun 2014–2025, relevan dengan etnosains, pembelajaran IPAS/IPA sekolah dasar, budaya lokal, kearifan lokal, pembelajaran kontekstual, praktik perkebunan atau pengolahan singkong, serta tersedia dalam teks lengkap. Data dianalisis menggunakan analisis deskriptif-tematik melalui identifikasi, pengelompokan, pemetaan, dan interpretasi tema-tema utama yang berkaitan dengan praktik lokal masyarakat dan konsep IPAS. Hasil kajian menunjukkan bahwa etnosains perkebunan singkong dapat diintegrasikan ke dalam pembelajaran IPAS melalui tiga bentuk utama, yaitu integrasi konseptual, integrasi kontekstual, dan integrasi nilai budaya. Integrasi konseptual tampak pada pemetaan praktik pemilihan bibit, stek batang, pengolahan tanah, perawatan tanaman, fermentasi tape, pengeringan gaplek, dan produksi tepung tapioka dengan konsep pertumbuhan tumbuhan, ekosistem, perubahan zat, dan proses produksi. Integrasi kontekstual dilakukan dengan memanfaatkan kebun singkong, lingkungan pertanian, dan industri rumah tangga sebagai sumber belajar. Integrasi nilai budaya mencakup penanaman nilai kerja keras, gotong royong, kemandirian ekonomi, dan kepedulian lingkungan. Implikasi kajian ini menunjukkan perlunya pengembangan perangkat pembelajaran IPAS berbasis etnosains singkong yang sistematis, kontekstual, dan sesuai dengan karakteristik siswa sekolah dasar di Tulang Bawang.